NATYA GANDES: INOVASI REPERTOAR JAIPONGAN KEMASAN SENI WISATA: Indonesia - Nuriawati, Risa; Azizah, Farah Nurul (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
The Natya Gandes dance is an innovative Jaipongan repertoire specifically created to cater to the demands of tourism-oriented performances in West Java. Developed through a practice-based research approach, this work preserves the essential structural components of traditional Jaipongan—bukaan, pencugan, nibakeun, and mincid. To appeal to a broader and more contemporary audience, Natya Gandes incorporates modern elements, including Zumba-inspired movements and digitally arranged traditional music. The title Natya Gandes symbolizes a graceful, energetic, and skilled female figure, reflecting the choreography’s expressive, interactive, and dynamic character. This article focuses on examining the conceptual framework underlying the choreography of Natya Gandes, offering a detailed analysis of its key components: movement vocabulary, spatial design, musical accompaniment, title and theme, genre and stylistic nature, performance method, number and gender of dancers, as well as makeup, costuming, and lighting. Ultimately, this choreographic innovation aims to enrich the traditional performing arts repertoire while simultaneously enhancing the appeal of West Javanese cultural heritage within the tourism sector.